Empowerment in business development through marketing expansion and business legality in Anugrah Art Batik Rembang - Damayanti Damayanti; Susiana Dwi Aprilia Kartini; Anisa Rizqi Artanti (Peneliti Teknologi Teknik Indonesia, 2022)
Batik is valued as the Indonesian nation’s identity and a part of Indonesian culture, specifically Javanese culture. There are various batik types, usually named after their origin place; one of them is Lasem's batik. Anugrah Art Batik, a member of micro-small-medium-enterprises, MSMEs, is one of Lasem's batik businesses that produce various written batik that serves orders for batik uniforms and designs in Kasreman Village, Rembang Regency, and Central Java. The challenges faced by Anugrah Art Batik are the lack of marketing management and business legality. Inadequate marketing resulted in lower-than-optimal sales. A community service program was carried out to help overcome the problems through Business Work Lectures, including creating banners and signs for the business, making batik catalog books, digital marketing by creating Facebook and Instagram accounts and managing business legality. The four programs were expected to increase sales according to the business target and hoped that it would be able to compete by continuing to develop its businesses.